17. THE SATISFACTION RATE OF OUTPATIENTS AT THE DEPARTMENT OF EXAMINATION, TIEN GIANG GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Background: asseessing patient satisfaction is an important criterion in Asseessing the quality of medical examination and treatment at medical facilities.Objective: describe the satisfaction rate of outpatients at the Department of examination, Tien Giang General Hospital in 2023.Methods: descriptive cross-sectional study, interviewing on 229 outpatients at the Department of examination, Tien Giang General Hospital, from July 2032 to December 2023.Results: the overall patient satisfaction rate reached 81.1%, the highest rate was the satisfaction rate about the attitude and professional competence of medical staff (86.81%), the lowest was the grassroots level materials facilities to serve patients (68.24%).Conclusion: soon relocate the hospital, add human resources to the social work deparment, promote propaganda on registration of the medical examination through the switchoboard.
Keywords: patient satisfaction; Tien Giang General Hospital.